2020
DOI: 10.1038/s41598-020-71177-6
|View full text |Cite
|
Sign up to set email alerts
|

Controlling oleogel crystallization using ultrasonic standing waves

Abstract: Oleogels are lipid-based soft materials composed of large fractions of oil (> 85%) developed as saturated and hydrogenated fat substitutes to reduce cardiovascular diseases caused by obesity. Promising oleogels are unstable during storage, and to improve their stability careful control of the crystalline network is necessary. However, this is unattainable with state-of-the-art technologies. We employ ultrasonic standing wave (USSW) fields to modify oleogel structure. During crystallization, the growing crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 46 publications
3
39
1
Order By: Relevance
“…By implying GC, Moghtadaei [82] concluded that the cooling temperature or the concentration of the structuring agent, namely beeswax, did not influence the fatty acid profiles of the oleogel sample, which was abundant in linoleic acid. High-intensity ultrasound application on a high oleic sunflower oil structured with myverol monoglicerides did not statistically affected the main composition [31].…”
Section: Chemical Characterization Of the Oleogelsmentioning
confidence: 73%
See 1 more Smart Citation
“…By implying GC, Moghtadaei [82] concluded that the cooling temperature or the concentration of the structuring agent, namely beeswax, did not influence the fatty acid profiles of the oleogel sample, which was abundant in linoleic acid. High-intensity ultrasound application on a high oleic sunflower oil structured with myverol monoglicerides did not statistically affected the main composition [31].…”
Section: Chemical Characterization Of the Oleogelsmentioning
confidence: 73%
“…Using synchrotron light X-ray diffraction, microcrystals of monoglycerides were revealed in the structure of an oleogel developed under ultrasonic standing waves, while in oleogels which crystallized in statical conditions, the microcrystals were absent. The monoglycerides in the sample treated with ultrasounds of 1 MHz, exhibited the triclinic β-form, and a lamellar thickness of 48 Å-49 Å was observed, while for the rest of the samples the thermodynamically stable form was observed, namely the hexagonal α-form with a slightly bigger lamellar thickness dimension [31].…”
Section: Oleogel's Building Unitsmentioning
confidence: 92%
“…The viscosity was higher for 12HSA organogels than that of the CW ones, which corroborated the microscopy findings earlier described. A more densely packed crystal network, such as seen for 12HSA organogels, can reduce the mobility of the components inside the organogels by increasing the tortuosity of the system [ 29 ]. Crystals acted as barriers against the organogel flow during the viscosity analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Images were saved in a temporary folder of Windows and should be transferred to the destination folder after completion of analysis. A 10% monoglyceride-based oleogel was selected here as an example of LBM (more information about the oleogel preparation procedure can be found in [7] ). After preparation, the oleogel was cut into cylinders (diameter: 20 mm, height: 7-10 mm, mass: 3.25 ± 0.5 g) using a metallic cylindrical shaper with thin walls and was placed on a filter-paper disk (Whatman filter paper #2 disk, material: cellulose, pore size: 8 µm, thickness: 190 µm, diameter: 15 cm), which was then placed on the tripod.…”
Section: Setupmentioning
confidence: 99%
“…The full sequence of images is presented in the supplementary material as a gif file (Oil Release GIF). Data were then fitted using a power law equation ( , where y is the total oil stain area, K is the rate constant, x is time, and n is the exponent; the procedure used is described in [7] ). The large number of data points coupled with the quality of the data yielded low-fitting errors on the estimated parameters ( Fig.…”
Section: Imagej Scriptsmentioning
confidence: 99%